PROCALCITONIN PREDICTS WELL ACUTE PYELONEPHRITIS AND RENAL SCARS IN CHILDRE WITH URINARY TRACT INFECTION - Leroy, Sandrine; Fernandez-Lopez, Anna; Nikfar, Roya; Romanello, Carla; Bouissou, Francois; Gervaix, Alain; Chalumeau, Martin (Oxford Univ Press, 2012)
[Abstract Not Available]
49th Congress of the European-Renal-Association/European-Dialysis-and-Transplant-Association (ERA-EDTA) -- MAY 24-27, 2012 -- Paris, FRANCE